2022
DOI: 10.3390/antiox11112153
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Hydrogen-Rich Water Improves the Nociceptive and Anxio-Depressive-like Behaviors Associated with Chronic Inflammatory Pain in Mice

Abstract: Chronic inflammatory pain is manifested in many diseases. The potential use of molecular hydrogen (H2) as a new therapy for neurological disorders has been demonstrated. Recent studies prove its analgesic properties in animals with neuropathic pain, but the possible antinociceptive, antidepressant, and/or anxiolytic actions of H2 during persistent inflammatory pain have not been investigated. Therefore, using male mice with chronic inflammatory pain incited by the subplantar injection of complete Freud’s adjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The injection of HRW into the abdominal cavity of male mice with chronic inflammatory pain can not only alleviate the inflammatory pain, but also inhibited the behaviors related to depression-like and anxiety-like behaviors. [71] Repeated inhalation of high concentrations of H 2 gas relieves stress-induced depression and anxiety in mice. [73] Saline enriched with H 2 had similar anxiolytic effects in morphine withdrawal mice.…”
Section: External Stimuli-responsive Gasotransmitter Prodrugsmentioning
confidence: 99%
See 3 more Smart Citations
“…The injection of HRW into the abdominal cavity of male mice with chronic inflammatory pain can not only alleviate the inflammatory pain, but also inhibited the behaviors related to depression-like and anxiety-like behaviors. [71] Repeated inhalation of high concentrations of H 2 gas relieves stress-induced depression and anxiety in mice. [73] Saline enriched with H 2 had similar anxiolytic effects in morphine withdrawal mice.…”
Section: External Stimuli-responsive Gasotransmitter Prodrugsmentioning
confidence: 99%
“…Endogenous Inhibition AG Schizophrenia [27] L-NOARG Schizophrenia [26] AG Depression [24] 7-NI Depression [22] Stimulation Heme-lysinate Depression [32] External External stimuliresponsive gasotransmitter prodrugs SNP Depression [34] SNP Schizophrenia [35] Molsidomine Depression [46] Molsidomine Schizophrenia [47] DETA/NONOate Depression [52] CORM-2 Depression [53] CORM-3 Depression [55] CO-rich saline or CO gas Depression [56] NaHS Depression [58] Na 2 S Depression [64] DADS Depression [67] Hydrogen-Rich Water Depression [71] Nano-gas carrier CORM-2-SLN Depression [54] These gas-related drugs can affect the development of depression and schizophrenia by either stimulating the production of gas or inhibiting its production. thus reduces cGMP production.…”
Section: Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent experiments further revealed that the therapeutic administration of hydrogen-rich water (HRW) has beneficial effects in animals with paclitaxel-induced neuropathic pain [37]. This treatment also reduced the nociceptive and emotive disturbances occasioned by nerve injury and persistent paw inflammation in male mice [38,39]. There is also evidence that H 2 exhibits antidepressant and/or anxiolytic properties in animals with traumatic brain injury [40] or chronic stress-induced depressive-and anxiety-like comportments [41] and further improves psychiatric illnesses in humans [42].…”
Section: Introductionmentioning
confidence: 99%